Analisis Kejadian ISPA Pada Balita di Puskesmas Bukit Sangkal Palembang Tahun 2023 - Wimalisca, Hane; Harokan, Ali; Zaman, Chairil; Dwi Priyatno, Akhmad (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
Acute Respiratory Infection (ARI) is an acute infection involving the upper and lower respiratory tract organs. This infection is caused by viruses, fungi and bacteria. This study uses a quantitative method approach with an analytical survey method and the research design used in this study is cross-sectional observation or data collection at one point (point time approach). The population in this study were parents with toddlers who came for treatment at the Bukit Sangkal Health Center in 2022, namely 2945 respondents. The research was conducted in May - June 2023 at the Bukit Sangkal Health Center. Sampling used a purposive sampling technique. The number of samples obtained was 100 respondents at the Bukit Sangkal Palembang Health Center. The results showed that the variables of birth weight, nutritional status, immunization status, educational factors, presence of smoking, and occupancy density were as follows: most of the respondents had normal birth weight 87 respondents (87.0%), normal nutritional status 64 respondents (64.0%), complete immunization status 72 respondents (72.0%), higher education factor 89 respondents (89.0%), presence of smoking 64 respondents (64.0%) who did not smoke, and dense occupancy density 77 respondents (77.0%). It is suggested to the Bukit Sangkal Health Center in Palembang City to improve the field of health services such as programs in the field of counseling and provide education on how to prevent the occurrence of ARI in toddlers.